Windfalls of emperors' sojourns: stock market reactions to Chinese firms hosting high-ranking government officials - Schuler, Douglas A. (2018)
We contribute to the corporate political activity (CPA) literature by showing that investors value companies that host visits of high ranking government officials (President and Premier). We argue that investors may value hosting firms for two reasons: (1) the signal received about possibility of firm accessing government-controlled resources via promotion or protection; and (2) the certification effect from such high powered visitors elevating the firm’s reputation and legitimacy. Results from an event study analysis of 84 high ranking government official visits in China from 2003 to 2011 indicate that investors responded positively to hosting firms, as reflected by stock market performance. Furthermore, the greatest positive reactions accrued to firms experiencing weaker prior period financial performance and to firms that are privately compared to state-controlled.